(untitled) (Development Service Industry Management, 2025)
The publication examines the issues of sustainable and stable functioning and development of enterprises. It is emphasized that in conditions of crisis and high level of socio-economic instability, the best method of ensuring the sustainable long-term functioning and development of a business entity is the management of its economic security. That is why the purpose of the study is to generalize existing and develop new methodological and applied solutions for the management and application of technologies for ensuring the economic security of an enterprise. It is argued that the economic security of a business entity should be considered as a state in which the following are simultaneously guaranteed: proper financial and economic sustainability of management, high level of financial and economic efficiency of functioning and development, provision of the enterprise with the necessary resources and assets, protection from existing and potential challenges, risks and threats. The directions, measures and structural divisions of the mechanism for ensuring the economic security of the enterprise have been determined. The mechanism for managing the economic security of the enterprise has been developed. The methodological and applied provisions for the formation of the system for managing the economic security of the enterprise have been outlined, in which a significant place is given to indicators for analyzing the state of the economic security of the enterprise. Measures have been identified, the implementation of which allows maintaining a high level of economic security of a business entity on a stable basis. The scientific novelty of the research results lies in the development of new management approaches to strengthening the economic security of enterprises and organizations. The applied significance of the results lies in the possibility of implementing measures aimed at bringing the enterprise onto the trajectory of sustainable and safe functioning and development.